Influence of trans fatty acids on glucose metabolism in soleus muscle of rats fed diets enriched in or deprived of linoleic acid - Fariña, Ana Clara (2018)
Purpose: Industrial trans fatty acid (TFA) intake leads to impaired glucose metabolism. However, the overall effects reported are inconsistent and vary with the dietary FA composition and TFA isomer type and levels. We investigated TFA effects on glucose uptake, incorporation and oxidation, and glycogen synthesis in incubated soleus muscle under basal conditions or after treatment with insulin and/or palmitate. Methods: Male Wistar rats were fed either linoleic acid (LA)-enriched (+LA) or LA-deprived (−LA) diet, supplemented (+LA + TFA or −LA + TFA) or not with TFA, for 60 days. Soleus muscle glucose metabolism was assessed in the absence or presence of insulin and/or palmitic acid. Results: Under basal conditions, TFA enhanced glucose uptake and oxidation regardless of the LA status. Both TFA-supplemented groups had lower insulin response to glucose metabolism. Under insulin-stimulated conditions, TFA prevented the palmitate inhibition of muscle glucose uptake and metabolism in the +LA + TFA group. Conclusion: Dietary TFA enhanced glucose utilization in incubated soleus muscle under basal conditions and prevented the palmitate-induced inhibition in insulin-stimulated conditions. However, TFA reduced the insulin response to glucose uptake and metabolism. The effects mentioned above were influenced by the FA profile modifications induced by the dietary LA levels, suggesting that lipid metabolization and incorporation into plasma membrane are important determining factors of glucose metabolism and insulin sensitivity.